Bloch-Kohn and Wannier-Kohn functions in one dimension - Bruno-Alfonso, A.; Hai, G. Q. (Iop Publishing Ltd, 2003)
Bloch and Wannier functions of the Kohn type for a quite general one-dimensional Hamiltonian with inversion symmetry are studied. Important clarifications on null minigaps and the symmetry of those functions are given, with emphasis on the Kronig-Penney model. The lack of a general selection rule on the miniband index for optical transitions between edge states in semiconductor superlattices is discussed. A direct method for the calculation of Wannier-Kohn functions is presented.